1973
DOI: 10.1007/bf00119104
|View full text |Cite
|
Sign up to set email alerts
|

Cytotaxonomy of the Lorisoidea (primates: Prosimii). I. Chromosome studies and karyological relationships in the Galagidae

Abstract: Chromosome studies were made in 33 specimens of the genus Galago, referable to the following seven species and subspecies: alleni, crassicaudatus crassicaudatus, crassicaudatus kikuyuensis, crassicaudatus monteiri, demidovii, senegalensis ssp. and senegalensis braccatus. The chromosome numbers and karyotypic structures found in these (sub)species are reported and described. Of six of them idiograms were constructed. All other available data on the cytology of the Galagidae are reviewed.The intraspecific variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 22 publications
6
42
0
Order By: Relevance
“…Chromosome banding data suggested that the differences between the karyotypes of these closely related species are simple Robertsonian translocations (de Boer, 1973;Dutrillaux et al, 1982;Rumpler et al, 1983). Chromosome painting confirmed this hypothesis, and comparing the results with the ancestral primate karyotype provided the information about the direction of changes in galagos.…”
Section: Lorisidaesupporting
confidence: 61%
“…Chromosome banding data suggested that the differences between the karyotypes of these closely related species are simple Robertsonian translocations (de Boer, 1973;Dutrillaux et al, 1982;Rumpler et al, 1983). Chromosome painting confirmed this hypothesis, and comparing the results with the ancestral primate karyotype provided the information about the direction of changes in galagos.…”
Section: Lorisidaesupporting
confidence: 61%
“…In karyotypic analyses, the number and gross structure of chromosomes is evaluated in order to develop parsimonious phylogenetic hypotheses. De Boer examined the chromosomes of galagos, and concluded that G. crassicaudatus preserved the most primitive karyotype [122]. G. senegalensis and G. alleni shared several specialized traits that linked them to each other [122].…”
Section: Molecular Evidencementioning
confidence: 99%
“…The traditional view is to accept an Asian clade and an African clade, while some researchers [87,121] have preferred instead a small-bodied clade (Arctocebus and Loris) contrasting with a large-bodied clade (Nycticebus and Perodicticus). Other suggested arrangements have Nycticebus and Arctocebus as a clade to the exclusion of Loris and Perodicticus [122][123][124], and finally Perodicticus as the outgroup to a clade of Arctocebus, Nycticebus and Loris [23]. The extant galagines certainly form a distinct clade when compared to the lorisines, but the internal relationships among galagines at the generic and specific levels remain controversial.…”
Section: Phylogeny Of Extant Lorisid Generamentioning
confidence: 99%
See 2 more Smart Citations